Aspek Profesionalisme dalam Pelayanan Publik: Kasus Pelayanan Pendidikan di Kota Padangpanjang - LANIN, DASMAN; SYAMSIR, SYAMSIR (Fakultas Ilmu Sosial Universitas Negeri Padang, 2012)
This study aims to describe the professionalism aspects of public service personnel at Department of Education in Padangpanjang City. This study uses a quantitative approach with the type of ex post-facto. The study population consisted of heads of household in Padangpanjang totaling 10,864 individuals and were spread in two districts and 16 villages. Sample was taken in two stages, cluster sampling and proportional stratified random sampling. Data were collected through questionnaires and analyzed using a statistical percentage, mean, and other central tendency according to research interests. Results of this study indicated that the professionalism of the public service personnel in the field of education in Padangpanjang is still not optimal. Kata Kunci: profesionalisme, pelayanan publik, pelayanan pendidikan